Penerapan Model Pembelajaran Kooperatif Tipe Make a Match Untuk Meningkatkan Motivasi Belajar Siswa Mata Pelajaran PKn Kelas III SDN 01 Mamben Daya - Muhammad Fadlurrahman; Nyoman Dantes; Desak Putu Parmiti (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aims to increase the learning motivation of PKN students by using a make a match type cooperative learning model at SDN 01 Mamben Daya. This type of research is a class action research (PTK) which is conducted in two cycles with the Kemmis & Mc Taggart research model consisting of four stages, namely planning, action, observation and reflection. The subject of this study is grade III students of SDN 01 Mamben Daya totaling 16 students in semester 2 of the 2024/2025 school year. The results of this study can be explained as follows: in the application of the make a match type cooperative learning model, there is an increase in student learning motivation in each cycle, which can be proven by the results of questionnaires and interviews that have been conducted on students. Where the results of the questionnaire showed that in the pre-cycle there were 4 students who were motivated with a classical percentage of 25% and an average student motivation of 48% while in the first cycle there were 9 students who experienced an increase in learning motivation with classical completeness of 56.25% and an average student learning motivation of 59%. Meanwhile, in cycle II there were 15 students who experienced an increase in learning motivation with a classical percentage of 93.75% and the average student learning motivation in cycle II was 74%. So that in the second cycle it was declared successful because the increase in student learning motivation has reached the previously agreed success criteria of 70%.